Desenvolvimento e avaliação de um programa de habilidades cognitivas e emocionais para promoção do equilíbrio trabalho-vida pessoal - Santos, Gabriela Trombeta (Universidade Federal de São Carlos, 2025)
Many workers struggle to conciliate paid work demands with the rest of their lives, leading to negative effects on their health and well-being. However, there are few studies evaluating the effectiveness of intervention programs to improve work-life balance, which makes it difficult for professionals, organizations and public policy makers to implement evidence-based interventions. The aims of this research were to: (a) develop an intervention program on work-life balance – "Caminho do Equilíbrio Trabalho-Vida", for use via a cell phone app, and (b) evaluate the usability, acceptability, and effects of this program. The program involves a sequential learning experience covering: (a) self-monitoring, (b) psychoeducation on topics related to balancing work and personal life demands, (c) activities to increase specific cognitive and emotional skills through mindfulness training, and (d) written activities to stimulate the analysis and development of plans for improving the fit between work and personal life involvements. First, the process of developing the program and the cell phone app is presented, including a systematic literature review on the effects of mindfulness programs on work-life balance. Second, the process of evaluating this program is described, based on two pilot studies and a randomized controlled trial (RCT). The RCT was conducted with 474 Brazilian workers over the age of 18, with access to Android or iOS cell phones. Participants were randomly assigned to the intervention group (who received the program via the app) or the control group. Although retention rates were low in both groups, there were statistically significant effects indicating gains, with moderate to large effect sizes, for the group using the app, compared to the control group. These gains included increases in: mindfulness (p < 0.001, d = 1.07), satisfaction with work-life balance (p < 0.001, d = 0.94), psychological detachment from work during off-work hours (p = 0.014, rb = 0.32), satisfaction with activities for relaxation (p = 0.003, rb = 0.38), satisfaction with work productivity (p = 0.002, d = 0.72), and levels of well-being (p = 0.019, d = 0.69), as well as a significant reduction of work-to-life interference (p < 0.001, d = 0.95). No significant differences were found between the groups concerning their perceptions of life-to-work interference or of the benefits of combining work-life involvements. Six weeks after completing the program, findings for the app group were still significantly better than on the pre-test, indicating that program benefits were maintained. The main contributions of this research include: (a) an analysis of the literature on the effectiveness of mindfulness-based programs for work-life balance, and the development of a model of the relationship between mindfulness and perceptions of balance, important to support the work of professionals in this area, (b) a methodological contribution involving the creation of a mindfulness program integrated with issues of work-life balance, and (c) the evaluation of the effects of this program, indicating its potential to promote the well-being of Brazilian workers.
Development and evaluation of a cognitive and emotional skills program to promote work-life balancel
Keywords: Conflito trabalho-família; Atenção plena; Avaliação de programas; Regulação emocional; CIENCIAS HUMANAS::PSICOLOGIA